2017
DOI: 10.3382/ps/pew499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and drug resistance of avian Eimeria species in broiler chicken farms of Zhejiang province, China

Abstract: In this study, coccidia were isolated and identified from 5 main poultry farms located in Zhejiang province, eastern China. The overall prevalence of Eimeria spp. was 30.7% (95 of 310). Five common species were observed: E. tenella, E. acervulina, E. maxima, E. necatrix, and E. mitis. Two isolates (HZ and QZ) were tested for sensitivity to 8 anticoccidial drugs using 4 indexes including anticoccidial index (ACI), percent of optimum anticoccidial activity (POAA), reduction of lesion scores (RLS), and relative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 23 publications
2
33
1
1
Order By: Relevance
“…are evidently spread worldwide [ 17 ]. Eimeria species have been found with different prevalence during regional surveys in France [ 18 ], Jordan [ 19 ], Romania [ 20 ], Brazil [ 21 ], or China [ 22 ]. Our findings are in agreement with previous reports that show E. tenella as the predominant species found in Asia [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…are evidently spread worldwide [ 17 ]. Eimeria species have been found with different prevalence during regional surveys in France [ 18 ], Jordan [ 19 ], Romania [ 20 ], Brazil [ 21 ], or China [ 22 ]. Our findings are in agreement with previous reports that show E. tenella as the predominant species found in Asia [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This incidence may reflect a case of coccidiostat resistance in the field. Nowadays, avian eimeriosis resistance to various commercial anticoccidial drugs is reported and reviewed worldwide [ 22 , 28 30 ]. This might be a concern since no scientific reports are published in Indonesia so far.…”
Section: Resultsmentioning
confidence: 99%
“…Anticoccidial resistance (ACR) is a widely recognised problem in poultry production ( Chapman, 1997 ; Stephan et al, 1997 ; Chapman and Jeffers, 2014 ; Lan et al, 2017 ), and has been reported for monensin, salinomycin, nicarbazin, halofuginone, robenidine, toltrazuril and diclazuril ( McDougald, 1981 ; Chapman, 1997 ; Stephan et al, 1997 ). ACR in poultry production is generally considered to be the result of intensive use of anticoccidials, which has led to loss of sensitivity to these drugs ( Peek and Landman, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monensin has been used for the treatment of renal coccidiosis, but is toxic in turkey and guinea fowl. 16 Reports on resistance of Eimeria isolates to anticoccidial drugs are increasing, [61][62][63][64] and rotation of anticoccidial drugs is recommended to minimize the risk of resistance. Natural products, such as cider vinegar, are also emerging as alternative strategies to control avian coccidiosis.…”
Section: Parasitic Nephritismentioning
confidence: 99%